Hyperglycaemia-induced miR-301a promotes cell proliferation by repressing p21 and Smad4 in prostate cancer. (1st April 2018) - Li, Xiaojuan; Li, Jun; Cai, Yi; Peng, Shubin; Wang, Jun; Xiao, Zhaoming; Wang, Yu; Tao, Yiran; Li, Jun; Leng, Qu; Wu, Dinglan; Yang, Shaodong; et al.
Abstract: Hyperglycaemia promotes the development of Prostate cancer (PCa). However, the roles of miRNAs in this disease process and the underlying mechanisms are largely unknown. In this study, we recruited 391 PCa patients in China and found that PCa patients with high level blood glucose (≥100 mg/dL) trended to have high Gleason score (GS ≥ 7). miRNA-301a levels were significantly higher in prostate cancer than that in normal prostate tissues. Hyperglycaemia or high glucose treatment induced miR-301a expression in prostate tissues or PCa cell lines. miR-301a suppressed the expression of p21 and Smad4, and subsequently promoted G1/S cell cycle transition and cell proliferation in vitro and xenograft growth in nude mice in vivo . Furthermore, knockdown of p21 and Smad4 mimicked the effects of miR-301a overexpression. Restoration of p21 and smad4 could interrupt the effects of miR-301a overexpression. Importantly, inhibition of miR-301a severely blocked high glucose-induced PCa cell growth both in vitro and in vivo . These results revealed a novel molecular link between hyperglycaemia and PCa. The miR-301a plays an important role in the hyperglycaemia-associated cancer growth, and represents a novel therapeutic target for PCa.